A relaç\~ao entre o crescimento econômico e as desigualdades regionais no Brasil - Jo\~ao Carlos Ramos Magalh\~aes; Pedro Jorge Holanda Alves (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This paper estimates the dispersion of GDP per capita among Brazilian municipalities, from 1920 to 2016, and between it's states, from 1939 to 2017, by Gini index calculus. The results confirm Williamson's hypothesis (1965), that the dynamic of regional inequalities describe an inverted U pattern throughout national economic development, with an inequality peak at the year of 1970. Calculus for each of the five Brazilian macro-regions showed important different dynamics, and Gini index decomposition revealed major changes in wealth rankings among Brazilian municipalities, from 1920 to 1970.
Keywords: R11; C14; C82; N9; O47; 330; regional inequalities; economic development; income convergency; a century data analisys